Exploration and Research on the Training Mode and Curriculum System of Nursing Professionals in Higher Vocational Colleges from the Perspective of "1 + X" - Weihong Li, Liping Yang, Fengyun Wang (Forest Chemicals Review)
This paper explores a new training mode of nursing professionals suitable for 1 + X certificate system. This paper focuses on the realization of the training goal of compound skilled nursing talents with "one specialty and multiple abilities". Firstly, this paper takes the "1 + X" certificate standard as the basis for the construction of nursing specialty, and reconstructs the talent training scheme of "documentary evidence integration". Secondly, this paper takes the content of "1 + X" certificate as the basis of professional curriculum construction, and constructs the professional core curriculum system of "curriculum certificate integration". This paper explores how to build a "new double qualified" teaching staff and speed up the construction of high-quality resources. The results of this study show that at this stage, nursing education should build a talent training mode of "documentary evidence integration" under the 1 + X certificate system. The method proposed in this paper can optimize the course structure and realize the teaching effect of "course certificate integration". This method improves teachers’ ability of "teaching, training and testing". The new training mode of nursing professionals under the 1 + X certificate system meets the synchronous peers of "1" academic education and "X" vocational training of nursing students, realizes the seamless connection between "1" and "X", and provides innovative ideas for the promotion and implementation of the pilot work of 1 + X certificate system in the field of national nursing education.